Trace Mn(II)-catalyzed periodate oxidation of organic contaminants not relying on any transient reactive species: The substrate-dependent dual roles of in-situ formed colloidal MnO2 - Zong, Yang; Shao, Yufei; Wenjie Ji; Zeng, Yunqiao; Jun Xu; Liu, Wen; Xu, Longqian; Wu, Deli (Chemical Engineering Journal, 2023)
Traditional advanced oxidation processes (AOPs) generally suffer from the inevitable deactivation of catalysts and the ineffective consumption of transient reactive species (TRSs) that compromise the efficiency in destructing aqueous contaminants. Herein, it was interestingly found that trace Mn(II) could robustly catalyze the oxidation of organic contaminants by periodate (PI), with the performance was much better than the representative TRSs-dominated AOPs (i.e., the Fe(II)-activated hydrogen peroxide, peroxymonosulfate (PMS), peroxydisulfate and PI processes). Multiple lines of evidence excluded the oxidative contributions of TRSs, instead the stoichiometric formation of colloidal MnO2 via the condensation of di-μ-oxo-bridged Mn(IV) cluster was confirmed by UV-vis, X-ray absorption near edge structure spectroscopy and density functional theory calculation. Dependent on the structure of substrate, MnO2 colloids solely or simultaneously served as oxidant and catalyst for the enhanced treatment performance. Benefiting from the non-TRSs-involved oxidation strategy and the catalytic effects of Mn species, the trace-Mn(II)/PI process even outperformed the Co(II)-activated PMS counterpart (i.e., one of the most efficient AOPs known at present) on oxidant utilization efficiency. This study not only elucidated the roles of Mn(II) and colloidal MnO2 in PI-mediated contaminant degradation, but also signified the superiority of trace catalyst-assisted process without TRSs involvement in avoiding undesired side reactions and maximizing oxidation efficiency.
Keywords: Colloidal MnO; Periodate; Stoichiometric efficiency; Trace catalyst; Transient reactive species